(untitled) (Journal of the College of Basic Education, 2023)
The emergence of the idea of ​​bimaristans (a) as places for the treatment of patients since the adoption of the courtyard of the Prophet’s MosqueIn Medina during the reign of the Prophet Muhammad, may God bless him and his family; And that in the Battle of the Trench asThe Messenger of God commanded to set up a tent in which to treat the wounded.Which took to include doctors and pharmacists later and the Umayyad caliph Al-Walid binAbd al-Malik was the first bimaristan in Damascus in the year 702/880 AD to treat the blind and lepers.As for the first Islamic bimaristan, it was built during the reign of Caliph Harun al-Rashid, when he called The caliph, the physician Jibril bin Bukhtishu`, to build a new bimaristan in Baghdad. Due to the importance of bimaristans and their development, we decided to study the humeral bimaristan because it isIn addition to being an educational bimaristan, it represents the treatment of patients in a way that is considered advanced in its timeBesides being a civilized manifestation of Islamic civilization that we must highlightIts features, therefore, we proceeded to this study.Founder of Bimaristan Abu al-Shuja’ is considered a fana, Khusraw ibn al-Hasan ibn Buwayh al-Buwayhi al-Dulaimi, known as (AdadState) for the year 272 A.H. - 44 A.H.) Tha. Of the flags of the sultans who had a prominent impact on the scientific movement in Baghdad in the centurythe fourth Hijri; In order to study an aspect of the scientific movement in the era of hisscientists and approach them; This research was achieved, which required the scientific method to be limitedTo pursue medical sciences. Which prompted me to choose this research; It is a sense of importanceThe history of this cultural side" and the fact that the era of Adud al-Dawla did not obtain its right of research